Comparative Phylogenetics of Papilio Butterfly Wing Shape and Size Demonstrates Independent Hindwing and Forewing Evolution. (7th April 2020) - Owens, H L; Lewis, D S; Condamine, F L; Kawahara, A Y; Guralnick, R P
Abstract: The complex forces that shape butterfly wings have long been a subject of experimental and comparative research. Butterflies use their wings for flight, camouflage, mate recognition, warning, and mimicry. However, general patterns and correlations among wing shape and size evolution are still poorly understood. We collected geometric morphometric measurements from over 1400 digitized museum specimens of Papilio swallowtails and combined them with phylogenetic data to test two hypotheses: 1) forewing shape and size evolve independently of hindwing shape and size and 2) wing size evolves more quickly than wing shape. We also determined the major axes of wing shape variation and discovered that most shape variability occurs in hindwing tails and adjacent areas. We conclude that forewing shape and size are functionally and biomechanically constrained, whereas hindwings are more labile, perhaps in response to disruptive selective pressure for Batesian mimicry or against predation. The development of a significant, re-usable, digitized data resource will enable further investigation on tradeoffs between flight performance and ecological selective pressures, along with the degree to which intraspecific, local-scale selection may explain macroevolutionary patterns. [Batesian mimicry; Lepidoptera; geometric morphometrics; museum specimens.]